Case Report Management of Vaginal Prolapse in Crossbreed Cattle (Simmental-Bali) in Mico Village, Palakka District, Bone Regency. - azifah cahyani; Nurdin, Muhammad Ardiansyah (Hasanuddin University, 2024)
Vaginal prolapse is a common reproductive disorder in cattle and buffalo. This is considered an emergency condition that must be treated immediately to avoid complications. This case study reports on the incidence of vaginal prolapse in crossbreed cows and the treatment performed when the prolapse is due to gestational age which has entered the third trimester where there is an increase in abdominal pressure due to the increasing size of the uterus. From the results of clinical signs obtained in the field, namely the vagina that looks hanging out of the vulva so that the animal feels uncomfortable and the cow with an arched back position because of whooping. The treatment is cleaning the vagina with antiseptic liquid, repositioning it manually and then suturing it by giving epidural anesthesia to prevent the organs from coming back out and administering antibiotics and vitamins. Keywords: prolapse, reposition, cow, uterus, vagina